Comparative Characterization of the Leaf Tissue of Physalis alkekengi and Physalis peruviana Using RNA-seq and Metabolite Profiling - Fukushima, Atsushi; Nakamura, Michimi; Suzuki, Hideyuki; Yamazaki, Mami; Knoch, Eva; Mori, Tetsuya; Umemoto, Naoyuki; Morita, Masaki; Hirai, Go; Sodeoka, Mikiko; Saito, Kazuki (Frontiers in Plant Science, 2016)
The genus Physalis in the Solanaceae family contains several species of benefit to humans. Examples include Physalis alkekengi (Chinese-lantern plant, hōzuki in Japanese) used for medicinal and for decorative purposes, and Physalis peruviana, also known as Cape gooseberry, which bears an edible, vitamin-rich fruit. Members of the Physalis genus are a valuable resource for phytochemicals needed for the development of medicines and functional foods. To fully utilize the potential of these phytochemicals we need to understand their biosynthesis, and for this we need genomic data, especially comprehensive transcriptome datasets for gene discovery. We report the de novo assembly of the transcriptome from leaves of P. alkekengi and P. peruviana using Illumina RNA-seq technologies. We identified 75,221 unigenes in P. alkekengi and 54,513 in P. peruviana. All unigenes were annotated with gene ontology (GO), Enzyme Commission (EC) numbers, and pathway information from the Kyoto Encyclopedia of Genes and Genomes (KEGG). We classified unigenes encoding enzyme candidates putatively involved in the secondary metabolism and identified more than one unigenes for each step in terpenoid backbone- and steroid biosynthesis in P. alkekengi and P. peruviana. To measure the variability of the withanolides including physalins and provide insights into their chemical diversity of Physalis, we also analyzed the metabolite content in leaves of P. alkekengi and P. peruviana at 5 different developmental stages by liquid chromatography-mass spectrometry. We discuss that comprehensive transcriptome approaches within a family can yield a clue for gene discovery in Physalis and provide insights into their complex chemical diversity. The transcriptome information we submit here will serve as an important public resource for further studies of the specialized metabolism of Physalis species.